Study on the Tooth Profile Parameters Design Method of Crown Gear Coupling for Helicopter Tail Folding Device - Miaomiao Li; Zhao Zhang; Xi Wang; Shuai Liu; Rupeng Zhu (Journal of Engineering)
Shipboard helicopter folding technology can increase the number of helicopters parked on board aircraft carriers. Crown gear coupling is the trend in helicopter tail rotor folding technology due to its ability to automatically and quickly engage and disengage helicopter tail rotors. This paper presents a method for the design of tooth parameters for crown gear coupling for folding devices. The model of the relationship between tooth shape parameters and angular displacement of the crown gear coupling and the model of the relationship between angular displacement and shaft line angle of the crown gear coupling were established, respectively, and the basic parameters of tooth shape and modified parameters of the crown gear coupling were designed. The correctness of the design method of the tooth parameters of the crown gear coupling for the folding device was also verified through motion simulation. The results of the study provide a theoretical basis for the design and optimization of crown gear couplings for folding devices.